Intimate Partner Violence : The Influence of Job Opportunities for Men and Women - Bhalotra, Sonia; Kambhampati, Uma; Rawlings, Samantha; Siddique, Zahra (World Bank, Washington, DC, 2020)
This study examines the association of unemployment variation with intimate partner violence using representative data from thirty-one developing countries, through 2005 to 2016. It finds that a 1 percent increase in the male unemployment rate is associated with an increase in the incidence of physical violence against women by 0.50 percentage points, or 2.75 percent. This is consistent with financial and psychological stress generated by unemployment. Female unemployment rates have the opposite effect, a 1 percent decrease being associated with an increase in the probability of victimization of 0.52 percentage points, or 2.87 percent. That an improvement in women's employment opportunities is associated with increased violence is consistent with male backlash. The study finds that this pattern of behaviours emerges entirely from countries in which women have more limited access to divorce than men.